Issues of Commercial Jurisdiction in the Context of Courts Specialization in Ukraine - BALIUK, Iryna; NAMIASENKO, Olga (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The research deals with the study of such complex issues of commercial legal proceedings as the formation and development of the concept of specialization of courts, the relationship between the concepts of judicial specialization and jurisdiction, the conflict of jurisdiction of commercial and civil courts, commercial and administrative courts. The study also examines the issues of the formation of the judicial system of Ukraine and commercial courts in the judicial system of Ukraine, the problem of the formation of judicial practice and powers of the Supreme Court, and determines the causes of the conflict of jurisdiction. Criteria determining the jurisdiction of specialized courts are considered.